Penerapan Media CADe SIMU untuk Meningkatkan Analisis Diagram Instalasi Motor Listrik Siswa - Rahmatul Makruf; Sukardi Sukardi (Jurnal Pendidikan Teknik Elektro, 2026)
This study aims to analyze the effectiveness of applying CADe SIMU media in improving students’ diagram analysis ability in the Motor Installation Elements subject at Vocational High Schools (SMK). The fundamental problem addressed is the students' low analytical capability resulting from the lack of digital simulation-based media integration in active learning. This research employed a quantitative approach with a one-group Pre-test and Post-test experimental design involving Grade XI Electrical Power Installation Engineering students. Data were collected through expert-validated objective tests and analyzed using descriptive and inferential statistics. The results revealed a significant improvement in students’ diagram analysis ability following the implementation of CADe SIMU media. Statistical analysis confirmed that the post-intervention performance increased substantially compared to the initial state. Furthermore, the students' final achievement consistently exceeded the determined minimum competency standards. This study concludes that CADe SIMU is an effective interactive simulation-based medium for vocational education. It not only strengthens analytical thinking and problem-solving skills but also enhances technological literacy, aligning with 21st-century vocational education goals.